Comparative Study of Water Flow in Nanopores with Different Quartz <semantics>(10<mover>1¯</mover>0)</semantics> Surfaces via Molecular Dynamics Simulations - Peng Zhou; Junyao Bao; Shiyuan Zhan; Xingjian Wang; Shaopeng Li; Baofeng Lan; Zhanbo Liu (Nanomaterials)
Dewatering and gas production are applied on a large scale in shale gas development. The fundamental mechanisms of water flow in shale nanoporous media are essential for the development of shale oil and gas resources. In this work, we use molecular dynamic simulations to investigate water flow in two different quartz surface (<semantics>(10<mover>1¯</mover>0)<mtext>-</mtext>α</semantics> and <semantics>(10<mover>1¯</mover>0)<mtext>-</mtext>β</semantics>) nanopores. Results show that the <semantics>(10<mover>1¯</mover>0)<mtext>-</mtext>β</semantics> surface exhibits stronger water molecule structuring with a structure arranged in two layers and higher first-layer adsorption density (2.44 g/cm3) compared to the (<semantics>(10<mover>1¯</mover>0)<mtext>-</mtext>α</semantics> surface (1.68 g/cm³). The flow flux under the <semantics>(10<mover>1¯</mover>0)<mtext>-</mtext>α</semantics> surface is approximately 1.2 times higher than that under the <semantics>(10<mover>1¯</mover>0)<mtext>-</mtext>β</semantics> surface across various pressure gradients. We developed a theoretical model dividing the pore space into non-flowing, adsorbed, and bulk water regions, with critical thicknesses of 0.14 nm and 0.27 nm for the non-flowing region, and 0.15 nm for the adsorbed region in both surfaces. This model effectively predicts velocity distributions and volumetric flow rates with errors generally below 5%. Our findings provide insights into water transport mechanisms in shale inorganic nanopores and offer practical guidance for numerical simulation of shale gas production through dewatering operations.